2006 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--914
|View full text |Cite
|
Sign up to set email alerts
|

One Step Beyond: Lecturing With A Tablet Pc

Abstract: is an instructional designer and e-Learning Support Specialist for Engineering Instructional Services at the Pennsylvania State University. In this capacity she supports faculty, teaching assistants and staff in developing technology skills and integrating those skills into courses and provides assistance in the areas of teaching, learning, instructional technology, and assessment. She received her B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Carter (2002) provides a framework that considers the needs of users (educators and learners) and provides suggestions on how multimedia systems can facilitate learning for each level of Bloom's taxonomy. Davies (2002) found that incorporating simulations into an engineering heat Ambikairajah et al, 2005;Anderson et al, 2004;Biswas, 2007;Derting & Cox, 2008;Frolik & Zum, 2004;James et al, 2006;Kamin et al, 2008;Mock, 2004;Sneller, 2007;Timmons, 2004Ambikairajah et al, 2005Lord & Perry, 2006;Pomales-Garcia & Liu, 2007;Stickel, 2008aStickel, , 2008bTimmons, 2004Ambikairajah et al, 2005Frolik & Zum, 2004;Lord & Perry, 2006;Mock, 2004Frolik & Zum, 2004Pomales-Garcia & Liu, 2007;Stickel, 2008a, 2008bDerting & Cox, 2008James et al, 2006;Timmons, 2004;Toto et al, 2007Biswas, 2007Gill, 2007;Mock, 2004Biswas, 2007Lord & Perry, 2006;Mock, 2004;Pomales-Garcia & Liu, 2007Biswas, 2007Mock, 2004Biswas, 2007Stickel, 2008a…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Carter (2002) provides a framework that considers the needs of users (educators and learners) and provides suggestions on how multimedia systems can facilitate learning for each level of Bloom's taxonomy. Davies (2002) found that incorporating simulations into an engineering heat Ambikairajah et al, 2005;Anderson et al, 2004;Biswas, 2007;Derting & Cox, 2008;Frolik & Zum, 2004;James et al, 2006;Kamin et al, 2008;Mock, 2004;Sneller, 2007;Timmons, 2004Ambikairajah et al, 2005Lord & Perry, 2006;Pomales-Garcia & Liu, 2007;Stickel, 2008aStickel, , 2008bTimmons, 2004Ambikairajah et al, 2005Frolik & Zum, 2004;Lord & Perry, 2006;Mock, 2004Frolik & Zum, 2004Pomales-Garcia & Liu, 2007;Stickel, 2008a, 2008bDerting & Cox, 2008James et al, 2006;Timmons, 2004;Toto et al, 2007Biswas, 2007Gill, 2007;Mock, 2004Biswas, 2007Lord & Perry, 2006;Mock, 2004;Pomales-Garcia & Liu, 2007Biswas, 2007Mock, 2004Biswas, 2007Stickel, 2008a…”
Section: Methodsmentioning
confidence: 99%
“…To achieve wireless connectivity with the projector, a wireless video device was located on the podium and connects to the projector via the video cable and to the tablet PC using Wi-Fi. There are several manufacturers of these devices and some recent projectors have a Wi-Fi link integrated into the unit, allowing a direct wireless connection from the tablet PC to the projector (Derting & Cox, 2008;Timmons, 2004;Toto et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations